Game development essentials : game interface design. - Saunders, Kevin D., ....-; Novak, Jeannie, 1966- (New York : Thomson, 2007)
As an introduction to the complicated topic os user interface design, this in-depth text discusses player interface design conventions and look at the effects of platform, genre, and design goals related to electronic games. Readers will explore everything from the history of game interface design and basic design theories to practical strategies for creating a winning, interactive interface. A host of professional applications, endearing insights, and illuminating anecdotes from dozens of pioneering game designers will inspire readers to explore this exciting industry.